Gordura protegida na terminação intensiva de bovinos a pasto - Silva, Edjane Pereira da (2023)
The objective was to evaluate the effects of the inclusion of protected fat in the diet of Nelore cattle on performance, feeding behavior, and carcass characteristics during the water period. Twenty-four uncastrated male cattle [30 ± 5 months and 454.0 kg ± 46.1, initial body weight (BW)] were block-weighed (2 blocks) and randomly distributed in twelve paddocks (2 animals per paddock) consisting of Brachiaria grass (Urochloa brizantha cv. Marandu) under continuous grazing system, assigned to receive one of the treatments: Control (CON) - concentrate supplied ad libitum without the addition of protected fat and Rumen Protected Fat (RPF) - concentrate supplied ad libitum with the addition of 3% protected fat (Blend, Nutricorp, Araras, São Paulo, Brazil). The concentrate was fed daily at 8:00 am and adjusted according to the leftovers. Before feeding the supplement, the leftovers (when there were) were collected and weighed. The experimental period lasted 105 days, divided into 4 periods. At the end of each period, forage was collected, animals were weighed, and feeding behavior was evaluated. After 105 days the animals were slaughtered in a commercial slaughterhouse, the carcass was divided into two similar halves, and three 2.54 cm steaks from the Longissimus dorsi (between the 12th and 13th rib) of each animal were collected to evaluate the color, chemical and physical composition, and sensory analysis. Means were compared by T-test and differences considered from P < 0.05 and trends were discussed when 0.05 ≤ P ≤ 0.10. There was an effect (P < 0.05) for forage quantitative and qualitative characteristics between experimental periods. The inclusion of protected fat in concentrate did not affect (P > 0.05) average daily gain, final body weight, concentrate intake, and feed efficiency of animals, but there was a trend (P ≤ 0.07) for higher carcass weight for animals receiving RPF. The inclusion of protected fat increased (P < 0.05) average daily carcass gain. There was no effect (P > 0.05) of treatments on the feeding behavior of the animals. However, grazing time was found to reduce over the experimental period. There was an effect (P < 0.05) of treatments on meat coloration. However, it can be concluded that RPF has the potential to improve the carcass characteristics and meat quality of beef cattle under an intensive pasture finishing system in the water period.